2018
DOI: 10.1089/thy.2017.0200
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation Genetic Diagnosis of Multiple Endocrine Neoplasia Type 2A Using Informative Markers Identified by Targeted Sequencing

Abstract: Targeted, capture-based next-generation sequencing for identification of informative markers together with Sanger sequencing is an easy and efficient method for the PGD of monogenic diseases such as MEN2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…regarding pregnancy termination (37). Compared to timely prophylactic thyroidectomy (PTT, discussed below), PGT-M is a primary prevention strategy which can avoid the transmission of diseases and families at risk from the source (38). However, the potential risk (such as implantation failure, multiple pregnancies, premature birth, etc.…”
Section: Prevention Of Men2mentioning
confidence: 99%
See 1 more Smart Citation
“…regarding pregnancy termination (37). Compared to timely prophylactic thyroidectomy (PTT, discussed below), PGT-M is a primary prevention strategy which can avoid the transmission of diseases and families at risk from the source (38). However, the potential risk (such as implantation failure, multiple pregnancies, premature birth, etc.…”
Section: Prevention Of Men2mentioning
confidence: 99%
“…As demonstrated in the ATA-2015, the clinicians should make patients aware of both the benefits and the potential risks of these technologies, and genetic counseling about these reproductive options should be considered for all patients carrying the RET mutations who are of reproductive age, particularly those having RET mutations in codons 634 and 918 (2). A simple and efficient method that involves targeted and capture-based next generation sequencing (T-NGS) for identification of informative markers including the entire RET coding region and 1 Mb range on each side of the gene together with Sanger sequencing has been established by our group for PGT-M of MEN2 (38). Using this method, one healthy baby whose father had MEN2A with the RET C634Y mutation was born without the inheritance of the mutation.…”
Section: Prevention Of Men2mentioning
confidence: 99%
“…In 2011, Altarescu et al reported of an Israeli woman with MEN 2A, who by the use of PGT-M, gave birth to genetically unaffected dizygotic twins (8). Chen et al presented a similar case of PGT-M in a Chinese couple where the male had MEN 2A (9). Unlike some other countries, in Denmark PGT is not reserved for specific diseases for which the procedure has been approved (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Adding to this, patients seem to have a genuine interest in PGT-M in relation to reproduction ( 7 ). However, just two cases have been reported so far and none originated from Europe ( 8 , 9 ). Aiming to increase awareness among physicians treating this and other genetic disorders, especially in Europe, of the possibility for PGT-M in MEN 2A patients, we here report the first European case.…”
Section: Introductionmentioning
confidence: 99%
“…This includes individuals with a pre‐existing genetic diagnosis, carriers of disease‐associated mutations or parents in whom previous pregnancies or offspring have been affected by genetic disease. Increasingly, pre‐implantation genetic diagnosis (PGD) may be offered in situations where parents are at risk of transmitting severe monogenic disorders and has been successfully employed in the context of MEN1, MEN2 and CAH . PGD is only possible in the context of in vitro fertilization (IVF) and involves the sequencing of DNA isolated from a small number of early blastocyst cells .…”
Section: Special Situations For Testingmentioning
confidence: 99%